The monocyte-to-osteoclast transition in rheumatoid arthritis: Recent findings - Iwamoto, Naoki; Kawakami, Atsushi (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint inflammation leading to joint destruction and deformity. The crucial role of osteoclasts in the bone erosion in RA has been demonstrated. Deregulated osteoclastogenesis which is affected by environmental factors including the inflammatory state, as well as genetic and epigenetic factors, is one of hallmarks of RA pathogenesis. An enhanced-monocyte-to-osteoclast transition plays an important role in osteoclast upregulation in RA because under specific stimuli, circulating monocytes might migrate to a specific location in the bones and fuse with each other to become mature multinucleated osteoclasts. To understand the mechanism of bone damage in RA and to develop novel treatments targeting osteoclast upregulation, it is important to clarify our understanding of the monocyte-to-osteoclast transition in RA. Several potential targets which inhibit both inflammation and osteoclastogenesis, as well as regulators that affect the monocyte-to-osteoclast transition have been revealed by recent studies. Here, we review the factors affecting osteoclastogenesis in RA, summarize the anti-osteoclastogenic effects of current RA treatments, and identify promising therapeutic targets relating to both inflammation and osteoclastogenesis.